Cause and effect consequences of industrial dispute - Ismail, Fadillah; Maulad Bahrol, Khadijah; Abdul Kadir, Adibah (Penerbit Uthm, 2019)
The Industrial Disputes Act, 1947 came into existence in April 1947. It was enacted to make provisions for investigation and settlement of industrial disputes and for providing certain safeguards to the workers. Some of workplace relationships invariably involve conflict or disputes. Some of this dispute will be processed through the machinery or conciliation or arbitration and will be settled by Industrial Relations. What is a “trade dispute”? The definition of a trade dispute was contained in the Trade Dispute Act (1906)